2019
DOI: 10.32479/ijeep.7987
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Autoregressive Integrated Moving Average-PHGMDH Model to Forecast Crude Oil Price

Abstract: Crude oil price fluctuations affect almost every individual and activity on the planet. Forecasting the crude oil price is therefore an important concern especially in economic policy and financial circles as it enables stakeholders estimate crude oil price at a point in time. Autoregressive integrated moving average (ARIMA) has been an effective tool that has been used widely to model time series. Its limitation is the fact that it cannot model nonlinear systems sufficiently. This paper assesses the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Due to nonlinear features, the classical time series models are not capable of predicting crude oil prices accurately [21]. erefore, inspired by the advantage of MEEMD in this study, a novel approach that integrates MEEMD-GMDH is used for forecasting crude oil price.…”
Section: The Proposed Meemd-gmdh Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to nonlinear features, the classical time series models are not capable of predicting crude oil prices accurately [21]. erefore, inspired by the advantage of MEEMD in this study, a novel approach that integrates MEEMD-GMDH is used for forecasting crude oil price.…”
Section: The Proposed Meemd-gmdh Modelmentioning
confidence: 99%
“…is study also concluded that the decision tree models achieved higher prediction accuracy than benchmark models such as multiple linR and ARIMA. Due to nonlinear features, the classical time series models were not capable of predicting crude oil prices accurately [21,22].…”
Section: Introductionmentioning
confidence: 99%